Active disturbance rejection control based human gait tracking for lower extremity rehabilitation exoskeleton. (March 2017) - Long, Yi; Du, Zhijiang; Cong, Lin; Wang, Weidong; Zhang, Zhiming; Dong, Wei
Abstract: This paper presents an active disturbance rejection control (ADRC) based strategy, which is applied to track the human gait trajectory for a lower limb rehabilitation exoskeleton. The desired human gait trajectory is derived from the Clinical Gait Analysis (CGA). In ADRC, the total external disturbance can be estimated by the extended state observer (ESO) and canceled by the designed control law. The observer bandwidth and the controller bandwidth are determined by the practical principles. We simulated the proposed methodology in MATLAB. The numerical simulation shows the tracking error comparison and the estimated errors of the extended state observer. Two experimental tests were carried out to prove the performance of the algorithm presented in this paper. The experiment results show that the proposed ADRC behaves a better performance than the regular proportional integral derivative (PID) controller. With the proposed ADRC, the rehabilitation system is capable of tracking the target gait more accurately. Highlights: ADRC was proposed to drive the rehabilitation exoskeleton to follow human gait trajectory. Simulations and experiments show ADRC is effective. ADRC has potentials to achieve promising performance in the preliminary rehabilitation stage.